PENERAPAN TEKNOLOGI SPRINKLER BERBASIS IOT PADA IRIGASI HOLTIKULTURA LAHAN KERING KEPULAUAN - Kalvein Rantelobo; Tomycho Olviana; Hendro F. J. Lami; Theodosius Laubase; Hevenly I. A. Berubu; Bernandus, Bernandus; Nixon Rammang, Nixon Rammang; Agusthinus Sampeallo (Journal of Innovation Research and Knowledge, 2025)
Agriculture is a vital sector for the majority of Indonesians, especially in regions with unique agroecological characteristics such as East Nusa Tenggara (NTT) Province. Existing conditions indicate that some agriculture in NTT's drylands is still rain-fed. One modern irrigation technology that offers a potential solution to overcome these challenges and is relevant for dryland conditions is the sprinkler irrigation system. This system operates by spraying water onto agricultural land in the form of fine droplets, resembling natural rainwater, thereby offering specific advantages over other systems. The development of digital technology presents opportunities to enhance the effectiveness and efficiency of sprinkler irrigation systems by integrating them with the Internet of Things (IoT). By utilizing IoT-based controllers, sprinkler systems can be operated, monitored, and managed remotely in real-time via smart devices, such as smartphones or mini-computers. The results of this Community Partnership Empowerment (CPE) activity indicate that the application of sprinkler irrigation technology can increase farmer productivity and reduce water consumption by approximately one cubic meter (m³) per week. The results are very suitable and have the potential to be applied in dryland areas such as NTT.